2014
DOI: 10.1007/s00167-014-3345-2
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-specific instrumentation improved mechanical alignment, while early clinical outcome was comparable to conventional instrumentation in TKA

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 67 publications
4
70
3
Order By: Relevance
“…Therefore, more well-designed, high-quality, long-term RCTs are needed monitor the survival of the prosthesis. A few studies showed a significant reduction in outliers of the mechanical alignment for PSI compared to SI [3, 11, 28, 33, 44]. However, in the present study, no evident difference in outliers of mechanical alignment was found between PSI and SI.…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore, more well-designed, high-quality, long-term RCTs are needed monitor the survival of the prosthesis. A few studies showed a significant reduction in outliers of the mechanical alignment for PSI compared to SI [3, 11, 28, 33, 44]. However, in the present study, no evident difference in outliers of mechanical alignment was found between PSI and SI.…”
Section: Discussioncontrasting
confidence: 83%
“…Reduction in the number of outliers from target rotational femoral component alignment indicates increased precision: controversial results have been obtained regarding this outcome, with some study groups reporting significant differences in favor of PSI and others not. Our study could not identify any difference in the proportion of outliers, both when following the “stricter” (±2°) and “looser” (±3°) criteria to define outliers proposed in the literature.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, a new technology that could reduce the proportion of incorrectly aligned implants appears appealing. However, there is controversy in the available published literature on the ability of PSI to affect the implant positioning, with some studies showing increased accuracy of femoral rotation with the use of PSI [8][9][10][11] and others revealing no differences from conventional alignment techniques [12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…At two years after surgery, the PSI group had a larger improvement in KSFS compared to conventional TKA. However, the KSKS, OKS and WOMAC were comparable between the two groups [13].…”
Section: Score (Kss) and Western Ontario And Mcmaster Universities Armentioning
confidence: 95%
“…There is a paucity of published literature on the clinical outcomes after PSI surgery [7][8][9][10][11][12][13]. Furthermore, these studies are also limited by their short follow-up periods.…”
mentioning
confidence: 99%